Valuation analysis of one share of GameStop Corp. - Matoušek, Martin (2022)
This thesis deals with the valuation analysis of one share of GameStop Corp. as of January 30, 2021 for the purpose of providing assistance to an individual investor in making investment decisions and answering the question of whether one of the share prices of GameStop Corp. before or after a short squeeze was close to its intrinsic value. The thesis contains, among other things, a description of the company, including its historical and expected future development, financial and strategic analysis relevant to the valued company, which is further used in developing a financial plan. The discounted cash flow method was chosen as the primary valuation method. The result of these analyses is a provided interval of indicative intrinsic value of one share of GameStop Corp., supplemented by additional sensitivity analyses and a pessimistic scenario indicating a minimum intrinsic value of the share. The conclusion of the thesis is that the price of the analysed share before or after the so-called short squeeze did not correspond to its intrinsic value and cannot be recommended as an investment to an individual investor as of the valuation date.